A musical intervention for respiratory comfort during noninvasive ventilation in the ICU. Issue 1 (17th January 2019) - Messika, Jonathan; Martin, Yolaine; Maquigneau, Natacha; Puechberty, Christelle; Henry-Lagarrigue, Matthieu; Stoclin, Annabelle; Panneckouke, Nataly; Villard, Serge; Dechanet, Aline; Lafourcade, Alexandre; Dreyfuss, Didier; Hajage, David; et al.
Discomfort associated with noninvasive ventilation (NIV) may participate in its failure. We aimed to determine the effect of a musical intervention on respiratory discomfort during NIV in patients with acute respiratory failure (ARF). An open-label, controlled trial was performed over three centres. Patients requiring NIV for ARF were randomised to either a musical intervention group (where they received a musical intervention and were subjected to visual deprivation during the first 30 min of each NIV session), a sensory deprivation group (where they wore insulating headphones and were subjected to visual deprivation during the first 30 min of each NIV session), or a control group (where they received NIV as routinely performed). The primary outcome was the change in respiratory discomfort before and after 30 min of the first NIV session. A total of 113 patients were randomised (36 in the musical intervention group, 38 in the sensory deprivation group and 39 in the control group). Median (interquartile range (IQR)) change in respiratory discomfort was 0 (−1; 1) between the musical intervention and control groups (p=0.7). Between groups comparison did not evidence any significant variation of respiratory parameters across time or health-related quality of life (HRQoL) at day-90. The Peri-traumatic Distress Inventory (PDI) at intensive care unit (ICU) discharge was reduced in musical intervention group patients. However, a 30 min musical intervention did not reduce respiratory discomfort during NIV for ARF in comparison to conventional care or sensory deprivation. A 30-min musical intervention in ARF patients requiring NIV decreases peri-traumatic symptoms at ICU discharge http://ow.ly/UVOE30myIbM